Avascular necrosis hips: management with core decompression bone graft and bone marrow aspirate concentrate - Jhunjhunwala, H. R.; Tawri, Pratik Sunil (International Journal of Research in Orthopaedics, 2023)
Background: Avascular necrosis of the femoral head is a disorder that can lead to the collapse of the femoral head and can progress to secondary osteoarthritis, which would ultimately require a total hip replacement. It can be avoided if the disease is diagnosed at an early stage. Intra-osseous pressures can be reduced, thereby aiding in halting the disease progression by core decompression along with bone marrow aspirate concentrate with morselized bone allograft. Aim was to evaluate the role of core decompression with BMAC with bone grafting for the treatment of early stage AVN of the hip by clinical and functional outcomes of the patient. Methods: A prospective observational study done to evaluate the clinical and functional outcomes by using the Harris hip score with domains for pain, functional activity, range of motion, and gait. Pre-operative and 18-months post-operative HHS was calculated in 30 samples between 30-50 years undergoing core decompression with BMAC and bone grafting in AVN hip upto Ficat Arlet stage IIb. Results: There was a significant increase in HHS from 67.66±9.87 pre-operatively to 92.4±7.4 post-operatively (p<0.05) which is statistically significant), indicates marked pain relief and functional well-being of the patients. Conclusions: Core decompression with BMAC and bone grafting is safe and effective in the early stages of AVN of the femoral head and is helpful in delaying the progression of AVN leading to THR based on clinical and functional outcomes of the patients at 18 months follow up.